Vision [videorecording (DVD)] : aus dem Leben der Hildegard von Bingen = from the life of Hildegard von Bingen - Trotta, Margarethe von; Sukowa, Barbara, 1950-; Ferch, Heino, 1963-; Herzsprung, Hannah; Striesow, Devid, 1973- (Zeitgeist Films, 2010)
The story of Hildegard von Bingen, a 12th century Benedictine nun, who was one of the first women to preach and interpret Biblical scripture.